Pengaruh Konten Gaya Hidup TikTok, Inklusi Keuangan, Self-Control terhadap Perilaku Konsumtif Gen Z - Aprilia Cesar; Asriany Asriany; Duriani Duriani (https://jurnal.binamandiri.ac.id/, 2026)
This study aims to analyze the influence of TikTok lifestyle content exposure, financial inclusion, and self-control on the consumptive behavior of Gen Z in North Luwu Regency. Utilizing a quantitative approach with purposive sampling, data were collected via surveys from 100 respondents aged 17–28 and analyzed using multiple linear regression with SPSS version 27. The results indicate that exposure to lifestyle content on TikTok has a positive and significant effect on consumptive behavior, whereas self-control has a significant negative effect. Financial inclusion was found to have no significant impact on consumption levels. These findings confirm that TikTok lifestyle content is the most dominant external factor driving consumptive behavior, while self-control acts as a critical internal moderator. This research underscores the importance of digital literacy and the strengthening of self-control to enable Gen Z to manage the influence of social media trends more wisely.